Alanis Obomsawin the Vision of a Native Filmmaker - Lewis, Randolph (University of Nebraska Press, 2006)
In more than twenty powerful films, Abenaki filmmaker Alanis Obomsawin has waged a brilliant battle against the ignorance and stereotypes that Native Americans have long endured in cinema and television.
OCLC: 1200868429
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Épistémologies autochtones; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Decolonizing the Lens of Power: Indigenous Films in North America - Kerstin, Knopf (Rodopi, 2008)
Knopf samples a variety of Native American filmmaking genres, including documentary, short films, and full-length narrative films, providing a detailed synopsis and content analysis of several films. Since its genesis in the early 19005, film has been an effective colonizing tool, impacting Indigenous peoples around the globe.
Issue: 4 Pages: 611-614
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Épistémologies autochtones; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé